2020
DOI: 10.1007/s10337-020-03945-5
|View full text |Cite
|
Sign up to set email alerts
|

Stability Indicating LC Method Development for Hydroxychloroquine Sulfate Impurities as Available for Treatment of COVID-19 and Evaluation of Risk Assessment Prior to Method Validation by Quality by Design Approach

Abstract: A quality by design-based stability indicating HPLC method has been developed for hydroxychloroquine sulfate impurities. The optimized HPLC method can detect and quantify the hydroxychloroquine sulfate and related organic impurities in pharmaceutical solid oral dosage forms. Nowadays, for the quantification of impurities in drug products demands more comprehensive way of analytical method development. The quality by design approach allows the assessment of different analytical parameters and their effects with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Doravirine, lamivudine, and tenofovir disoproxil fumarate were stable under forced photolytic and neutral degradations. In the degradation studies, peak purity test results derived from the photodiode-array detector (Dongala et al, 2020) confirmed that the peaks of doravirine, lamivudine, and tenofovir disoproxil fumarate were homogeneous and pure in all the analyzed stress samples. The stressed samples results are presented in Table 7.…”
Section: Forced Degradation Studiesmentioning
confidence: 62%
See 1 more Smart Citation
“…Doravirine, lamivudine, and tenofovir disoproxil fumarate were stable under forced photolytic and neutral degradations. In the degradation studies, peak purity test results derived from the photodiode-array detector (Dongala et al, 2020) confirmed that the peaks of doravirine, lamivudine, and tenofovir disoproxil fumarate were homogeneous and pure in all the analyzed stress samples. The stressed samples results are presented in Table 7.…”
Section: Forced Degradation Studiesmentioning
confidence: 62%
“…The stability studies were conducted by exposing the dosage form to different stress conditions such as acid, base, peroxide, thermal, light, and water (Dongala et al, 2019;Katakam & Dongala, 2020a,b). The dosage form was slightly degraded in acid, base, peroxide, and thermal conditions, but remained stable in photolytic and hydrolytic conditions.…”
Section: Forced Degradation Studiesmentioning
confidence: 99%
“…At the end of each period in each test, degraded samples were tested and reviewed. None of the samples degraded in any of the studies (Dongala et al, 2019(Dongala et al, , 2020Naresh et al, 2020). The forced degradation results are shown in Table 3.…”
Section: Physical Degradation Experimentsmentioning
confidence: 88%
“…23 Also, HCQ and LVX have been described as a combination treatment in cutaneous manifestations in patients with COVID-19. Numerous HPLC [25][26][27][28][29][30][31][32][33][34][35] and spectrouorimetric 36 studies have been reported to analyze each cited drug alone or with other drugs. Till now, only two HPLC methods 34,35 and one spectro-uorimetric method 36 have been reported to determine two of the mentioned drugs, RDV and HCQ, together.…”
Section: Scientistsmentioning
confidence: 99%